The Process of Developing a Disease Activity Index in Microscopic Colitis. (25th September 2021) - Lesnovska, Katarina Pihl; Münch, Andreas; Bonderup, Ole; Magro, Fernando; Kupcinskas, Juozas; Zabana, Yamile; Tontini, Gian Eugenio; Munck, Lars Kristian; Guagnozzi, Danila; Latella, Giovanni; Fernandez-Banares, Fernando; Miehlke, Stephan; et al.
Abstract: Background and Aims: Patient-reported outcome measures [PROMs] aim to measure patients' perception of how their disorder influences everyday functioning. The objective of this study was to develop a PROM to assess disease activity in microscopic colitis [MC] fulfilling the requirements of the Food and Drug Administration [FDA]. Methods: The European Microscopic Colitis Activity Index [E-MCAI] was developed in four steps. [1] A list of symptoms associated with active MC was created by a group of experts in the field. [2] Content validity of the symptoms was performed by experts [ n = 14] and patients [ n = 79] using the Content Validity Index. [3] Questions and response alternatives were created for each symptom, and validity of the E-MCAI was evaluated with cognitive interviews with patients [ n = 7] and by the experts. [4] A pilot postal survey was performed to ensure usability. Results: Seven of the symptoms related to active MC fulfilled the criteria for content validity and were included in the E-MCAI: stool consistency, stool frequency, stools at night, feel a need to pass more stools shortly after a bowel movement, urgent need to empty the bowel, leakage of stool and abdominal pain. The development and validation process resulted in the current version of the E-MCAI consisting of six questions related to MC. Conclusions: The E-MCAI was developed using the methods advocated by the FDA. The evaluation indicates good content validity. Further evaluation will be performed to achieve construct validity, reliability and responsiveness in future cross-sectional and longitudinal studies.